COVID-19: Literature review and its impact on the Peruvian health reality - Córdova-Aguilar, Alberto (2020)
Introduction: The disease called COVID-19 is a pandemic caused by the SARS-CoV-2 virus (severe acute respiratory syndrome 2). In Peru, patient zero or first case with COVID-19 was detected on March 6 and since then the virus has continued to spread. The national government fights against this disease on several fronts, but the health situation differs greatly from developed countries. Objective: To review the current state of the disease and analyze its possible impact on the Peruvian health system. Methods: A bibliographic search of various studies was carried out since the appearance of the disease (December 2019) in the different databases (PUBMED, MEDLINE, PLOs, SciELO) and in Google Scholar. Results: It was found that the virus is transmitted mainly by the respiratory route; the average incubation period is 14 days; most patients have mild disease or are asymptomatic but 5% of these will require hospitalization, some will even require intensive therapy with mechanical ventilation; the current treatment is basically symptomatic, but antibiotics, antivirals and antiparasitics have also been used. Conclusions: The quarantine with strict measures of isolation and social distancing is accurate given the Peruvian health reality and the imminent contagion of the population.